Sieci innowacyjne a małe i średnie przedsiębiorstwa - Poznańska, Krystyna (Innovative Networks and Small and Medium-Sized Enterprises, 2006)
The article an analysis of the theoretical aspect of the innovative networks is done. It is a common opinion that the small and medium-sized enterprises have a considerable potential for creating group and innovative networks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 136-143